Penerapan Teknik Penataan Cahaya pada Produksi Drama Televisi "Analog" - Iman, Naufal Luthfi; Astuti, Aprilina Dwi; Kristiadi, David (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
Television drama is often known as sinetron (Indonesian soap opera), since the plot story is short but it conveys message that describe social life or daily life. Television drama requires proper lighting. Inappropriate lighting arrangement could make the information is not conveyed clearly to the audience. The author found that there are several shortcomings in terms of technical lighting in several television dramas such as in the first series of Ada Apa Dengan Cinta, Dua Garis Biru, and Before Sunrise. The shortcomings appeared in those dramas regarding light intensity that was over exposed, ineffective lighting arrangements and others. To overcome this problem, television drama "Analog" applied the three point of light technique as a basic lighting set-up and applies the artificial light technique as artificial light to convey time background information. In implementing this technique the author uses Godox SL200W and GVM 560AS lighting which are equipped with lighting support equipment such as diffuser filters, CTB filters and CTO filters. The application of the three point of light technique and artificial light technique makes the television drama "Analog" have the right lighting quality. As the result, the drama has an artistic impression and background information that can be conveyed clearly to the audience.